2018
DOI: 10.1111/agec.12411
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of smallholder participation in horticultural export chains: evidence from Ecuador

Abstract: We study the dynamics of smallholder participation in export value chains focusing on the example of small-scale broccoli producers in the highlands of Ecuador. Combining cross-sectional data from a household survey with 11-year longitudinal data on export market transactions, we explain the hazards of dropping out of a high-value export chain. We apply a multispell cox duration model that allows us to consider multiple entries and exits from the supply chain. We also provide evidence on the welfare impacts as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 31 publications
0
13
0
3
Order By: Relevance
“…Academic literature has discussed the impact of contracts on income and welfare (Bellemare, 2012; Narayanan, 2014), productivity, and efficiency (Mishra, Shaik, Khanal, & Bairagi, 2018), reducing transaction costs (Key & Runsten, 1999) and strengthening coordination in modern supply chains (Maertens & Swinnen, 2009; Schipmann & Qaim, 2010). Although participating in a CFA may seem beneficial for farmers' welfare, empirical studies have found that farmers drop out from contract schemes after initial engagement (Andersson, Chege, Rao, & Qaim, 2015; Romero Granja & Wollni, 2018). The unsustainability of the CFA in developing countries results from behavioral opportunism, combined with a contract design that fails to meet the preferences of both parties (Barrett et al, 2012; Oya, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Academic literature has discussed the impact of contracts on income and welfare (Bellemare, 2012; Narayanan, 2014), productivity, and efficiency (Mishra, Shaik, Khanal, & Bairagi, 2018), reducing transaction costs (Key & Runsten, 1999) and strengthening coordination in modern supply chains (Maertens & Swinnen, 2009; Schipmann & Qaim, 2010). Although participating in a CFA may seem beneficial for farmers' welfare, empirical studies have found that farmers drop out from contract schemes after initial engagement (Andersson, Chege, Rao, & Qaim, 2015; Romero Granja & Wollni, 2018). The unsustainability of the CFA in developing countries results from behavioral opportunism, combined with a contract design that fails to meet the preferences of both parties (Barrett et al, 2012; Oya, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The Inca berry network is an emerging chain located in the Highland region, which is characterized by the expansion of its production units in the last years [25]. This chain employs around 2000 of rural workers who participate in activities such as soilconditioning, transportation, and transformation of raw material [26]. Also, 98 percent of firms involved are SMEs 2 [27], which look for an opportunity for a superior market positioning.…”
Section: Introductionmentioning
confidence: 99%
“…El progreso de las cadenas agroalimentarias ecuatorianas también puede sufrir fallas de mercado y un bajo nivel de colaboración (Notarnicola et al, 2012;Romero Granja & Wollni, 2019). Por ejemplo, las cadenas emergentes como la de la uchuva presentan probabilidades relacionadas con el poder impuesto por las grandes empresas en las cadenas de suministro (Ruiz, 2018;Vega-Quezada et al, 2017) y el nivel de coordinación entre los actores (Banco Central de Ecuador, 2018; Observatory of Economic Complexity [OEC], 2017; Ministerio de Agricultura de Ecuador, 2014;Romero & Wollni, 2018). Por lo tanto, la comunidad cientíca debe considerar los aspectos mencionados al evaluar el desempeño de las cadenas de suministro de frutas y verduras.…”
Section: Introductionunclassified
“…La red de uchuva es una cadena emergente ubicada en la región de las tierras altas, que se caracteriza por la expansión de sus unidades de producción en los últimos años (Senplades, 2015). Esta cadena emplea a alrededor de 2000 trabajadores rurales que participan en actividades como el acondicionamiento del suelo, el transporte y la transformación de la materia prima (Romero & Wollni, 2018). Más aun, 98 % de las empresas involucradas son pequeñas y medianas (pymes) (Sarango-Lalangui et al, 2018) y buscan una oportunidad para mejorar su posicionamiento en el mercado.…”
Section: Introductionunclassified